Analysis of Sound Frequency on Guzheng Using Advanced Spectrum Analyzer Pro - Haris Rosdianto; Sumarli Sumarli; Suryati Suryati (JIPF (Jurnal Ilmu Pendidikan Fisika), 2021)
Physics learning about sound frequency will be more effective if equipped with practicum activities. This practicum activity can be done by linking it with a cultural because cultural values have the potential to be implemented in physics learning, such as musical instruments for sound frequency. As for the culture used in this research is the Guzheng. This research aims to analyzed  of the Guzheng sound frequency, the comparison of the sound frequency to the prime tones, and the comparison of the sound frequency to the octave tones. The research type that was used is based on laboratory experiment with the aids of Advanced Spectrum Analyzer Pro application which is already installed in the smartphone to measure the sound frequency of 21 strings of Guzheng. The result of the analyzed showed that the longer of string  so the sound frequency produced is the lower. As for of simple linear regression test showed that the sound frequency is linearly distributed to the prime tones and to the octave tones. The result of research can be applied in physics learning by conducting practicum activities and utilizing technology by the Advanced Spectrum Analyzer Pro application to measure the sound frequency both on musical instruments and on other objects that can make a sound.